IMPROVEMENT OF POWER QUALITY USING LOA BASED UPQC CONTROLLER IN HYBRID SYSTEM - et. al, Rama Subbanna S (International Journal of Advanced Science and Technology, 2020)
This paper presents the concept regarding the improvement of power quality in grid interfaced system using statcom regulator. The causes for effecting the power quality is changes in load, system conditions and changes in system parameters. In literature, there are so many methods/techniques implemented to improve power quality of the system. The unified power quality conditioner plays a vital role in the present scenario. The UPQC is a combination of two back to back converters. A suitable control circuit is developed for controlling the converters with the help of reference signals from the bus and dc link capacitor parameters. A linear optimization based algorithm has been proposed in this paper for better controlling of dc link capacitor voltage. The proposed system is implemented and tested in Matlab/Simulink.